Intraoperative autologous transfusion and oncologic outcomes in liver transplantation for hepatocellular carcinoma: a propensity matched analysis. Issue 3 (March 2022) - Sutton, Thomas L.; Pasko, Jennifer; Kelly, Gabrielle; Maynard, Erin; Connelly, Christopher; Orloff, Susan; Enestvedt, C. Kristian
Abstract: Background: Intraoperative autologous transfusion (IAT) of salvaged blood is a common method of resuscitation during liver transplantation (LT), however concern for recurrence in recipients with hepatocellular carcinoma (HCC) has limited widespread adoption. Methods: A review of patients undergoing LT for HCC between 2008 and 2018 was performed. Clinicopathologic and intraoperative characteristics associated with inferior recurrence-free (RFS) and overall survival (OS) were identified using Kaplan–Meier analysis and uni-/multi-variable Cox proportional hazards modeling. Propensity matching was utilized to derive clinicopathologically similar groups for subgroup analysis. Results: One-hundred-eighty-six patients were identified with a median follow up of 65 months. Transplant recipients receiving IAT (n = 131, 70%) also had higher allogenic transfusions (median 5 versus 0 units, P  < 0.001). There were 14 recurrences and 46 deaths, yielding an estimated 10-year RFS and OS of 89% and 67%, respectively. IAT was not associated with RFS (HR 0.89/liter, P  = 0.60), or OS (HR 0.98/liter, P  = 0.83) pre-matching, or with RFS (HR 0.97/liter, P  = 0.92) or OS (HR 1.04/liter, P  = 0.77) in the matched cohort (n = 49 per group). Conclusion: IAT during LT for HCC is not associated with adverse oncologic outcomes. Use of IAT should be encouraged to minimize the volume of allogenic transfusion in patients undergoing LT for HCC.